Analisis Financial Distress pada Perusahaan Sub Sektor Telekomunikasi yang Terdaftar di Bursa Efek Indonesia Periode 2018-2022 - Anastashia Maharani Muhadi; Anwar Ramli; Nurman Nurman; Hety Budiyanti; Andi Mustika Amin (Journal of Management and Creative Business, 2024)
The purpose of this study was to analyze the conditions of the possiblity of financial distress in telecommunication sub-sector companies listed on the Indonesia Stock Exchange for the period 2018-2022. The research sampling method used purposive sampling method. There are 18 telecommunication sub-sector companies that meet the sampling criteria that were previously determined. Secondary data is used in this study, namely in the form of annual financial reports of telecommunication sub-sector companies listed on the Indonesia Stock Exchange in 2018-2022. The Grover model approach (G-Score) in indetifying financial distress is used in this study. The research findings show that number of telecommunication sub-sector companies experienced financial distress between 2018-2-2022. The main causes of financial distress include insufficient working capital, high liabilities, and declining profitability.